Joe Death and the graven image - Schipper, Benjamin (Dark Horse Books, 2021)
"After surviving a brutal massacre, the last surviving heir of the town of Hard Hollow is kidnapped by the bloodthirsty bandit, Scary Harry. The spirit of Hard Hollow enlists Joe Death--a six-shooter-totin' grim reaper--to rescue the child"--